Natural hybridization in heliconiine butterflies: the species boundary as a continuum (2007)
Background To understand speciation and the maintenance of taxa as separate entities, we need information about natural hybridization and gene flow among species. Results Interspecific hybrids occur regularly in Heliconius and Eueides (Lepidoptera: Nymphalidae) in the wild: 26–29% of the species of Heliconiina are involved, depending on species concept employed. Hybridization is, however, rare on a per-individual basis. For one well-studied case of species hybridizing in parapatric contact (Heliconius erato and H. himera), phenotypically detectable hybrids form around 10% of the population, but for species in sympatry hybrids usually form less than 0.05% of individuals. There is a roughly exponential decline with genetic distance in the numbers of natural hybrids in collections, both between and within species, suggesting a simple 'exponential failure law' of compatibility as found in some prokaryotes. Conclusion Hybridization between species of Heliconius appears to be a natural phenomenon; there is no evidence that it has been enhanced by recent human habitat disturbance. In some well-studied cases, backcrossing occurs in the field and fertile backcrosses have been verified in insectaries, which indicates that introgression is likely, and recent molecular work shows that alleles at some but not all loci are exchanged between pairs of sympatric, hybridizing species. Molecular clock dating suggests that gene exchange may continue for more than 3 million years after speciation. In addition, one species, H. heurippa, appears to have formed as a result of hybrid speciation. Introgression may often contribute to adaptive evolution as well as sometimes to speciation itself, via hybrid speciation. Geographic races and species that coexist in sympatry therefore form part of a continuum in terms of hybridization rates or probability of gene flow. This finding concurs with the view that processes leading to speciation are continuous, rather than sudden, and that they are the same as those operating within species, rather than requiring special punctuated effects or complete allopatry. Although not qualitatively distinct from geographic races, nor 'real' in terms of phylogenetic species concepts or the biological species concept, hybridizing species of Heliconius are stably distinct in sympatry, and remain useful groups for predicting morphological, ecological, behavioural and genetic characteristics.